2020
DOI: 10.1101/2020.01.27.921536
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Protective Population Behavior Change in Outbreaks of Emerging Infectious Disease

Abstract: During outbreaks of emerging infections, the lack of effective drugs and vaccines increases reliance on non-pharmacologic public health interventions and behavior change to limit human-to-human transmission. Interventions that increase the speed with which infected individuals remove themselves from the susceptible population are paramount, particularly isolation and hospitalization. Ebola virus disease (EVD), Severe Acute Respiratory Syndrome (SARS), and Middle East Respiratory Syndrome (MERS) are zoonotic vi… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
14
0
2

Year Published

2020
2020
2021
2021

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 10 publications
(17 citation statements)
references
References 28 publications
1
14
0
2
Order By: Relevance
“…Community behavior is one of the crucial factors to avoid a higher number of cases and deaths from viral infections 8,25 . South Korea and Japan had already shown a flat curve of disease progression through restrictive measures 26,27 .…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Community behavior is one of the crucial factors to avoid a higher number of cases and deaths from viral infections 8,25 . South Korea and Japan had already shown a flat curve of disease progression through restrictive measures 26,27 .…”
Section: Discussionmentioning
confidence: 99%
“…On the other hand, Iran and Italy delayed taking these measures or had difficulty in controlling the people's obedience, and started to count many sick or dead people 26,27 . However, behavioral change depends on the context and is difficult to predict due to social characteristics, socioeconomic, and behavioral differences among people 8,28 . Unlike European and Asian countries, Brazil has little experience with catastrophes and calamities, with no local culture for preventing these situations.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Since the 2019-nCoV (COVID-19) outbreaks in Wuhan, China, the cumulative number of confirmed cases is increasing every day, and a large number of populations all over the world are at risk. The recent study [1][2][3][4] on the efficacy of traffic blockage for the COVID-19 indicated that the the population flows will certainly increase the cumulative number of cases and the quarantine and traffic blockage will lower this risk.…”
Section: Introductionmentioning
confidence: 99%